Reichsparteitag Nürnberg NSDAP Propaganda Postkarte Nuremberg Party... - Uncredited artist.... (Wikimedia Commons, 1938)
Carte postale ancienne issue de Wikimedia Commons. Titre: Reichsparteitag Nürnberg NSDAP Propaganda Postkarte Nuremberg Party Rally postcard issued by Photo Hoffmann MünchenEmblems of NSKK SA NSFK RAD DAF SS HJ SA NS Frauensch. Parteiadler No known copyright restrictions. Postcard of the Nuremberg Rally (German: Reichsparteitag Nürnberg) 1938. Emblems of the DAF (Deutsche Arbeitsfront, German Labour Front), SS (Schutzstaffel), RAD (Reichsarbeitsdienst, Reich Labour Service), NSKK (Nationalsozialistisches Kraftfahrkorps,, National Socialist Motor Corps), NSFK (Nationalsozialistisches Fliegerkorps, National Socialist Flyers Corps), HJ (Hitlerjugend, Hitler Youth), SA (Sturmabteilung), and NS-Frauenschaft (National Socialist Women's League). Also Parteiadler der NSDAP ('Nazi Party eagle'). Postcard issued by Photo Hoffmann München. No known copyright restrictions. The annual rally of the Nazi Party (NSDAP) were large propaganda events, especially after Adolf Hitler's rise to power in 1933. These events were held at the Nazi party rally grounds in Nuremberg, Germany from 1933 to 1938.
Licence Creative Commons Attribution-Share Alike 4.0 via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons